Water Quality Changes during the Initial Operating Phase of Riverbank Filtration Sites in Upper Egypt - Rifaat Abdel Wahaab (Water, 2019)
To meet the increasing water demand and to provide safe drinking water in Egypt, the Holding Company for Water and Wastewater (HCWW) and its affiliated companies have started a program to develop riverbank filtration (RBF) sites in all Egyptian governorates. The paper gives an overview of water quality changes as a result of RBF, during the initial phase of operation at three sites in Upper Egypt, between 2015 and 2018. Significant changes were observed for chloride, sulfate, iron, manganese, ammonium, and in the bacterial counts. After the initiation of pumping from the RBF wells, it took 2 to 8 months until stable water quality was observed for the hydrochemical parameters and 2 to 14 months for the microbiological parameters. The results showed that RBF wells should be operated continuously, to maintain the advantage of lower Fe and Mn concentrations achieved by the wash-out effect in the aquifer zone, between the river bank and the RBF wells.